Optimisation of characteristics of patin fish oil in alginate beads using central composite design-response surface methodology - Haris @ Harith, Muhammad Salahuddin; Noor Azam, Noor Ain Nasuha; Abror, Alya Alivia; Estiasih, Teti; Mohd Rus, Shaiqah (Malaysian Institute of Chemistry, 2024)
Omega-6 and omega-3 polyunsaturated fatty acids (PUFA), which are beneficial for human health and infant development, are abundant in patin fish. However, consuming it as a staple dish is unpleasant for individuals, especially children. As patin fish oil contained in micrometre size alginate beads would be convenient for children to consume, this study aims to optimise the size and sphericity of the beads. The major parameters, sodium alginate concentration, Tween 80 concentration and dripping flow rate, were investigated. A Central Composite Design (CCD)- Response Methodology Surface (RSM) technique was used to optimise the characteristics of the beads, and 19 formulation runs were performed. The bead size and sphericity index data from each run were gathered and analysed using software. The optimised formulation was validated and found to have insignificant difference (p>0.05). The optimised model produced by the program was achieved using a sodium alginate concentration of 3.94 % (w/v), Tween 80 concentration of 3.34 % (v/v), and dripping flow rate of 3.07 mL/min. The optimised beads were consistent in both size and sphericity index, which were 4.566 ± 0.043 mm and 0.933 ± 0.015, respectively. The size of the beads was not impacted by any of these factors. However, the sphericity of the beads was affected by the Tween 80 concentration and flow rate. The beads were proven to be nearly spherical with a non-porous structure, as shown by scanning electron microscope images. It is hoped that these beads could be an alternative approach to deliver patin fish oil for convenient consumption.